2017
DOI: 10.1063/1.5000126
|View full text |Cite
|
Sign up to set email alerts
|

Interface Si donor control to improve dynamic performance of AlGaN/GaN MIS-HEMTs

Abstract: In this letter, we have studied the performance of AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors (MIS-HEMTs) with different interface Si donor incorporation which is tuned during the deposition process of LPCVD-SiNx which is adopted as gate dielectric and passivation layer. Current collapse of the MIS-HEMTs without field plate is suppressed more effectively by increasing the SiH2Cl2/NH3 flow ratio and the normalized dynamic on-resistance (RON) is reduced two orders magnitude after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Zhu et al have demonstrated that the surface diffusion of Si is insufficient to compensate for the electron concentration and enhance performance [26]. On the contrary, etching damage accompanied by the diffusion of Si into the semiconductor will generate a leakage current path through the gate, affecting the reverse characteristics of the device [27]. The formation of TiN in high-temperature annealing can promote ohmic metal formation by ensuring direct contact with 2DEG or by forming N vacancies reported by many reports [28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al have demonstrated that the surface diffusion of Si is insufficient to compensate for the electron concentration and enhance performance [26]. On the contrary, etching damage accompanied by the diffusion of Si into the semiconductor will generate a leakage current path through the gate, affecting the reverse characteristics of the device [27]. The formation of TiN in high-temperature annealing can promote ohmic metal formation by ensuring direct contact with 2DEG or by forming N vacancies reported by many reports [28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results, we suppose that LPCVD can effectively prevent the diffusion of Si. Zhu et al have demonstrated that the surface diffusion of Si is insufficient to compensate for the electron concentration and enhance performance[26].On the contrary, etching damage accompanied by the diffusion of Si into the semiconductor will generate a leakage current path through the gate, affecting the reverse characteristics of the device[27].B. Formation Mechanism of Ohmic Contact…”
mentioning
confidence: 99%
“…A trade-off between gate leakage and current collapse as the Si/N ratio varied has been reported by Waller et al [25,26]. Song et al [27] revealed that the hysteresis of V th and the dynamic performance of AlGaN/GaN MIS-HEMTs can be improved by a Si-rich LPCVD-SiN x passivation layer. Huang et al observed an enhanced V th stability and low gate leakage of AlGaN/GaN MIS-HEMT devices with LPCVD-SiN x bilayer stacks using Si-rich SiN x (2 nm) as an interfacial layer capped with a high-resistivity SiN x (15 nm) layer [28].…”
Section: Introductionmentioning
confidence: 87%
“…Such a large discrepancy in the V th shift suggests the strong effect of SiN stoichiometry on the gate stability of MIS-HEMT devices. A Si-rich SiN x layer tends to result in higher gate stability [27], and the stability can be further enhanced by optimizing the thickness ratio. The sample with a 5 nm/15 nm SN1/SN2 bilayer stack (γ = 0.25) presents the most stable V th (e.g.…”
Section: Pressurementioning
confidence: 99%
See 1 more Smart Citation